Intellectual property rights in the Philippine case: In search of a moral justification using Filipino virtue ethics - Cruz, Christopher E. (Animo Repository, 2019)
This paper is an attempt to formulate an alternative way of upholding the existence of intellectual property rights that may be more acceptable to the Filipino mind. While the traditional arguments may be successful in defending the existence of intellectual property rights in the other countries, particularly the west, the same is not necessarily true in the Philippines, mainly because the traditional arguments do not give due consideration to the Filipino mind. Drawing its inspira-tion from the Sikolohiyang Filipino movement which seeks to analyze social realities (like intellec-tual property) from the Filipino perspective and not from western models, this paper shall attempt to provide an alternative justification1 to upholding the existence of intellectual property rights in the Philippines using Filipino indigenous knowledge, particularly Filipino Virtue Ethics. For this purpose, the paper shall use the framework of Dr. Michael J. Sandel and argue that his first two tests of “maximizing welfare” and “respecting freedom” represent the traditional arguments for defending intellectual property rights and that his third test of “promoting virtue” (justice as culti-vating virtue and reasoning about the common good) provide the appropriate framework for this study. It will argue that Sandel’s “promoting virtue” (justice as cultivating virtue) using Filipino virtue ethics is the better approach in upholding intellectual property rights in the Philippines. To understand Filipino virtue ethics, a discussion of the Filipino Mind through the Sikolohiyang Fili-pino framework pioneered by Dr. Virgilio G. Enriquez, an advocate of indigenous Filipino psy-chology, shall be used to explain why western models do not resonate with the Filipino mind. The paper will show that arguments based on Filipino core virtues of “Loob and Kapwa” and Filipino specific virtues like “kagandahang loob”, “hiya”, and “utang na loob” provide a better alternative in upholding intellectual property rights in the Philippine case because the Filipinos can better relate to them. These Filipino virtues will then be applied to specific cases to promote intellectual property rights in the Philippines, including the three major intellectual property issues facing the world today. In the end, the paper will conclude that the arguments promoting intellectual property rights based on “Promoting Filipino virtue ethics” (justice as valuing Filipino virtue ethics) will lead to better understanding and social acceptance of intellectual property rights in the Philippines.